2022
DOI: 10.3389/fpubh.2021.736424
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ideal Cardiovascular Health and Executive Function in Chinese Primary School Children

Abstract: Aims: Little information exists on the associations of cardiovascular health, a new metric proposed by the American Heart Association, and executive function, particularly in children. We aimed to explore this topic.Methods: We studied 3,798 children aged 6–12 years from 5 schools in Guangzhou, China. The executive function of children was evaluated using parent reports of the Behavioral Rating Inventory of Executive Function, which included 2 composite indexes and 8 subscale scores. We calculated the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“… Drozdowska et al (2021) observed a weak but significant positive correlation between speed (20-m sprint) and FT reaction time performance in a German study of 211 preadolescents ( 46 ). CRF (predicted VO 2max ) is generally reported to be associated with EF performance in Chinese preadolescents ( 42 , 47 ). The possible mechanism is that participants who exhibited better physical fitness had better cerebral oxygenation ( 48 , 49 ), and cognitive processing critically depends on adequate blood flow to meet the energy and oxygen demands of the brain's cortical tissue ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“… Drozdowska et al (2021) observed a weak but significant positive correlation between speed (20-m sprint) and FT reaction time performance in a German study of 211 preadolescents ( 46 ). CRF (predicted VO 2max ) is generally reported to be associated with EF performance in Chinese preadolescents ( 42 , 47 ). The possible mechanism is that participants who exhibited better physical fitness had better cerebral oxygenation ( 48 , 49 ), and cognitive processing critically depends on adequate blood flow to meet the energy and oxygen demands of the brain's cortical tissue ( 50 ).…”
Section: Discussionmentioning
confidence: 99%